Promoting Personal Growth through Experiential Learning: The Case of Expressive Arts Therapy for Lecturers in Thailand - Binson, Bussakorn; Lev-Wiesel, Rachel (Frontiers in Psychology, 2018)
The aim of the paper is to assess academic experiential learning in relation to academic lectures’ perceived personal and professional growth. Sixteen PhD students (age ranged between 23-46, 10 male, 6 females) participated in an introduction to expressive art therapy." Qualitative methods according to phenomenological methodology was used. At the beginning and end of the 48-hour course they were asked to draw themselves, and explain the differences between the two drawings. In addition participants were semi-structured interviewed about the course and its personal and professional aspects at the end of the course. The main themes were the carousal of emotional experience, the use of art means for growth, and, professional growth. Findings revealed a perceived growth in terms of family relationships, inter – personal skills, and professional role performance.